Pendidikan Holistik Islam Perspektif KH. Abdul Wahid Hasyim - Fadillah, Muti'ah; Kartika, Resti Okvani (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2024)
This research aims to explore K.H. Abdul Wahid Hasyim's thoughts about Islamic holistic education. Islamic holistic education is an educational approach that includes spiritual, intellectual, emotional and physical aspects in overall individual development. This writing applies qualitative techniques through library research. The data presented in this paper originated from the thoughts of KH. Abdul Wahid Hasyim spread in many books and articles. The findings from this study are that K.H. Abdul Wahid Hasyim has forward thinking ideas in about Islamic holistic education. His thoughts on character education are also relevant in the context of contemporary Islamic education. In this holistic education, Wahid Hasyim emphasizes five things, including overall individual development, integration of Islamic knowledge and values, contextual learning, strengthening spirituality and building a just society. His thoughts can be a reference in developing holistic Islamic education, which includes the development of all aspects of an individual's life